Usage of paper per student of UNHEVAL - 2011 - Hilario Cárdenas, Jorge (2017)
This research study was development by a research group which approached to determinate the index paper usage per student of the Universidad National Hermilio Valdizan during 2011, due to the lack of information about this issue and the importance such information due to its value as a environmental manage tool. For that development it was necessary to determinate a sample from the student population registered during 2011; the sampling resulted in a set of subsamples which were represent by the function of the quantity of students represented from every professional academic school in the academic headquarters of the university. To collect date it was use the survey which was validated by the research group and determinate its reliability through the pilot group of students. The development of this research establish that every student of the UNHEVAL use in average 951 sheets of paper Bond per year, and if this result is transformed into function of the quantity of raw material necessary in paper production process, the result evolve that it is necessary the feeling of 530  trees of 15 years age per year. This result proves that the University as a knowledge generator and therefore development should be pioneer of environmental protection by taking actions which reduce the usage of paper in its own institution and avoid being a polluting agent and the succeeding environmental depletion.